Perancangan dan Pembuatan Aplikasi Harga Pokok Produksi Dengan Metode Job Proccess Costing Untuk PT. X - Harijono, Chandra Kusuma Putra; Setiawan, Alexander; Setiabudi, Djoni Haryadi (Jurnal Infra, 2014)
PT.X is a company engaged in the production and distribution of slippers. At this time the recording of Data in PT.X is still manual. The calculation of the cost of production is also done manually, in the calculation of cost of production, which is calculated only the cost of materials only. Of the problems the cost of production, will lead to difficulties in calculating the profits and losses of the company. Based on these problems, then designed a system that can help the calculation of the cost of production. system design process starts from a number of stages, beginning with a survey to the company to analyze the slippers production process, analysis of existing data and designing the Data Flow Diagram and Entity Relationship Diagram of the application to be made. The process of making use of Microsoft Visual Studio. NET 2010 and SQLServer 2012 database. The results of this application is the recording of all data related to the production process, raw material purchase, sale sandals, calculating the cost of production is automated and also card stock that is updated automatically.